Jatoba (Hymenaea courbaril L.) Pod Residue: A Source of Phenolic Compounds as Valuable Biomolecules - Gabriela Lucca Del Angelo; Isabela Silva de Oliveira; Bianca Rodrigues de Albuquerque; Samanta Shiraishi Kagueyama; Tamires Barlati Vieira da Silva; José Rivaldo dos Santos Filho; Maria Inês Dias; Carla Pereira; Ricardo C. Calhelha; Maria José Alves; Ariana Ferrari; Natalia Ueda Yamaguchi; et al. (Plants)
This study aimed at investigating the chemical composition and a selected group of bioactivities of jatoba (Hymenaea courbaril L.) pod residue. An aqueous extract (deionized water; AE) and a hydroethanolic extract (ethanol: deionized water, 70:30 v/v; ETOH) were obtained via maceration. Ten phenolic compounds were characterized via LC-DAD-ESI/MSn: seven procyanidins, two quercetin derivatives and one taxifolin derivative, with dimers and trimers of procyanidins being the main components of both extracts. Total phenolic compound levels of 2.42 ± 0.06 and 11 ± 1 mg/g were found in AE and ETOH, respectively; however, only seven compounds were identified in ETOH. The jatoba pod residue extracts showed notable antioxidant activities: ETOH had greater antioxidant potential in the OxHLIA and DPPH assays (IC50 = 25.4 μg/mL and 0.71 μg/mL, respectively); however, EA demonstrated greater potential in the FRAP system (IC50 = 2001.0 µM TE/mg). Only AE showed antiproliferative potential, being effective against cell lines of gastric (GI50 = 35 ± 1 µg/mL) and breast (GI50 = 89 ± 4 µg/mL) adenocarcinomas. Likewise, only AE showed modest anti-inflammatory potential (IC50 = 225 ± 2 µg/mL) in mouse macrophages. Bacteriostatic effects against bacteria were exerted by both extracts. Enterococcus faecalis and Listeria monocytogenes (MICs = 2.5 mg/mL) were especially sensitive to the ETOH extract. Taken together, the results suggest potential for jatoba pod residue as a source of molecules with biological activities and with possible industrial applications.